Rola nauczania i dokształcania w readaptacji społeczno- -zawodowej osadzonych - Gertruda Wieczorek (Edukacja Ustawiczna Dorosłych)
Societies develop rules and norms of social coexistence that have to be observed because they guarantee social order. Penalties help maintain social balance and ensure the safety of all individuals. However, there are people who threaten others with anti-social behavior, and consequently, a system of penalties and sanctions are essential. One can risk a statement that the level of development of a given social group depends on the type of penalties applied in it.